Cloning and characterization of feline islet glucokinase - Lindbloom-Hawley, Sara; LeCluyse, Michelle; Vandersande, Vanessa; Lushington, Gerald Henry; Schermerhorn, Thomas (My University, 2014)
Glucokinase (GK) is a metabolic enzyme encoded by the GCK gene and expressed in glucose-sensitive tissues, principally pancreatic islets cell and hepatocytes. The GK protein acts in pancreatic islets as a “glucose sensor” that couples fluctuations in the blood glucose concentration to changes in cellular function and insulin secretion. GCK and GK have proposed importance in the development and progression of diabetes mellitus and are potential therapeutic targets for diabetes treatment. The study was undertaken to determine the nucleotide sequence of feline pancreatic GK cDNA, predict the amino acid sequence and structure of the feline GK protein, and perform comparative bioinformatic analysis of feline cDNA and protein. Routine PCR techniques were used with cDNA from feline pancreas. Clones were assembled to obtain the full length cDNA. Protein prediction and modeling were performed using bioinformatic tools.
Citation: Lindbloom-Hawley, S., LeCluyse, M., Vandersande, V., Lushington, G. H., & Schermerhorn, T. (2014). Cloning and characterization of feline islet glucokinase. BMC Veterinary Research, 10(1), 130. https://doi.org/10.1186/1746-6148-10-130
Keywords: Glucose sensor; Pancreas; Carbohydrate metabolism; Hexokinase; Gene expression